El cacicazgo en la región pampeana-norpatagónica argentina a mediados del siglo XVIII. La actuación de los caciques en torno a la instalación de las misiones jesuíticas - Irurtia, María Paula (2008)
Between 1740 and 1754 the Society of Jesus established three missionsin the south of the frontier that shaped the Salado river in the present territory of the State of Buenos Aires, Argentina. Concerning the colonial authorities the sites operated as advance post; for the indigenous groups they became a place of encounter, barter and confrontation and pacific dealings, where caciques (chiefs) played a fundamental role. I propose to identify the caciques that went to the missions, their purposes and strategies; to define a model of actions on a certain context and interests. A critic reading has been done from the documents concerning this Jesuit attempt and it has been confronted with the bibliographical production from different authors. It was possible to display the strategic approach to the missions, the kind of bonds that made possible this dynamic and different components which were part of the chiefdomship, specially, the hechicero (sorcerer). The chiefdomship in the middle of the 18th Century in Pama-North-Patagonia has been characterized as a dynamic form of leadership that operated in different levels and could be assumed by several persons in different circumstances.